A comparative study of LRRK2, PINK1 and genetically undefined familial Parkinson's disease. Issue 4 (2nd September 2009) - Nishioka, Kenya; Kefi, Mounir; Jasinska-Myga, Barbara; Wider, Christian; Vilariño-Güell, Carles; Ross, Owen A; Heckman, Michael G; Middleton, Lefkos T; Ishihara-Paul, Lianna; Gibson, Rachel A; Amouri, Rim; Ben Yahmed, Samia; et al.
Abstract : Genetic classification of Parkinson's disease (PD) subtypes may become the preferred diagnostic tool for neurologists. Herein we compare clinical features from a large cohort of patients with familial PD of unknown aetiology or attributable to distinct genetic forms. Comprehensive neurological examinations were performed in 231 familial PD patients from Tunisia. Analysis was previously performed to screen for mutations in leucine rich repeat kinase 2 ( LRRK2 ), PTEN induced kinase 1 ( PINK1 ) and parkin ( PRKN ). Clinical features were compared between patients with genetically undefined PD (n=107) and those with LRRK2 (n=73) and PINK1 (n=42) mutations using regression analyses adjusted for gender, age of onset and disease duration. PRKN cases (n=9) were too few for meaningful statistical analysis. In comparison with genetically undefined patients, LRRK2 mutation carriers had more severe motor symptoms (median Unified Parkinson's Disease Rating Scale scores ∼1.6 times higher, p<0.001), a higher rate of dyskinesia (OR 4.21, p=0.002) and use of dopamine agonists (OR 3.64, p<0.001), and less postural tremor (OR 0.21, p<0.001). PINK1 mutation carriers presented an increased rate of drug induced dyskinesia (OR 3.81, p=0.007) and a lower rate of postural tremor (OR 0.16, p<0.001) than genetically undefined patients. As expected, PINK1 patients had younger ages and ages at disease onset, and a longer disease duration compared with LRRK2 mutation carriers and genetically undefined patients. Clinical differences between LRRK2, PINK1 and genetically undefined familial PD appear more pronounced than previously appreciated, and may prove useful in clinical practice. As future therapies are targeted to specific protein abnormalities, identifying the genetic causes and associated clinical and pathological features will determine diagnosis, preventative medicine and drug intervention strategies.